Analiza regulacji prawnych w zakresie wykorzystania GMO - Stępień, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim of this article is to present and analyse the regulation of international law, EU law and Polish law, related to GMOs. The most important moment for the creation of international regulations was the adoption of the Convention on Biological Diversity. Within the EU there are lots of directives and regulations to protect against the risks related to the use of GMOs. In Poland there is the lack of acomprehensive law in the field of genetic engineering, currently there are several acts adopted in the form of alaw, which relate to various aspects of GMOs.
Keywords: GMO; prawo międzynarodowe; prawo unijne; polskie prawo